LANDASAN FILSAFAT SEBAGAI BASIS PENGAMBILAN KEPUTUSAN STRATEGIS DALAM MANAJEMEN PENDIDIKAN - Dedy Hartanto; Rizki Gagah Perkoso; Juliansyah; Muhammad Amir Masruhim; Dwi Nugroho Hidayanto; Warman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explain the role of philosophical foundations—ontology, epistemology, and axiology—as a basis for strategic decision-making in educational management. Using a descriptive qualitative approach through contemporary literature analysis, the findings reveal that these three philosophical dimensions function integratively in shaping the direction, knowledge mechanisms, and ethical values underlying educational policies. Ontology provides orientation regarding the essence of education and institutional purpose; epistemology offers a knowledge framework and data-driven foundation for decisions; while axiology safeguards ethics, justice, and human values in policy implementation. The results are visualized through bar charts, pie charts, radar charts, and concept maps to illustrate the relationships among dimensions. The study concludes that the quality of strategic decisions is highly dependent on how well educational leaders understand and integrate these philosophical dimensions. Such integration is essential for creating visionary, knowledge-based, and ethically grounded policies in responding to modern educational challenges.